2014
DOI: 10.1590/1678-6532
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade de ixodida em roedores e marsupiais capturados no Parque Estadual da Pedra Branca, Rio de Janeiro, Brasil

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
2
4
0
6
Order By: Relevance
“…All tick-host associations recorded here had previously been reported elsewhere in Brazil (BARROS-BATTESTI et al, 2006;SARAIVA et al, 2012;SZABÓ et al, 2013;GUGLIELMONE et al, 2014;OLIVEIRA et al, 2014;KRAWCZAK et al, 2016b;MARTINS et al, 2016;, except for records of A. longirostre on Trinomys dimidiatus and B. torquatus. This tick species has wide distribution throughout the Neotropical region, and its adults have commonly been reported parasitizing rodent species, especially of the genus Coendou (BARROS-BATTESTI et al, 2006;NAVA et al, 2010;.…”
Section: Discussionsupporting
confidence: 67%
“…All tick-host associations recorded here had previously been reported elsewhere in Brazil (BARROS-BATTESTI et al, 2006;SARAIVA et al, 2012;SZABÓ et al, 2013;GUGLIELMONE et al, 2014;OLIVEIRA et al, 2014;KRAWCZAK et al, 2016b;MARTINS et al, 2016;, except for records of A. longirostre on Trinomys dimidiatus and B. torquatus. This tick species has wide distribution throughout the Neotropical region, and its adults have commonly been reported parasitizing rodent species, especially of the genus Coendou (BARROS-BATTESTI et al, 2006;NAVA et al, 2010;.…”
Section: Discussionsupporting
confidence: 67%
“…The species richness was similar to our study; however, the species composition showed a few differences. Oliveira et al (2012) reported Marmosops incanus (Lund, 1840), Philander frenatus (Olfers, 1818), and Guerlinguetus brasiliensis (Gmelin, 1788), which were not captured in the present study, although the last one was visually recorded in 2001. Moreover, G. microtarsus was captured in the present study, but not in Oliveira et al (2012).…”
Section: Discussionmentioning
confidence: 57%
“…Oliveira et al (2012) reported Marmosops incanus (Lund, 1840), Philander frenatus (Olfers, 1818), and Guerlinguetus brasiliensis (Gmelin, 1788), which were not captured in the present study, although the last one was visually recorded in 2001. Moreover, G. microtarsus was captured in the present study, but not in Oliveira et al (2012). Considering all the information gathered, we may consider a total of 11 wild non-volant small mammals observed in PBSP so far, excluding the two invasive Rattus species.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…(PINTER, 2007;OGRZEWALSKA et al, 2014;MARTINS et al, 2016b). (HORTA et al, 2007;PINTER, 2007;OGRZEWALSKA et al, 2012b;SZABÓ et al, 2013;OLIVEIRA et al, 2014). (HOOGSTRAAL, 1967;LONDOÑO, 1976;KRINSKY, 1983;SERRA FREIRE, 1983;JONGEJAN, 1999;COUTO et al, 2015;ARAUJO et al, 2016;CARTER et al, 2016).…”
Section: Construção Dos Mapasmentioning
confidence: 99%